Mechanism-Based Cardiac Regeneration Strategies in Mammals - Naqvi, Nawazish; Iismaa, Siiri E.; Graham, Robert M.; Husain, Ahsan (Frontiers in Cell and Developmental Biology, 2021)
Heart failure in adults is a leading cause of morbidity and mortality worldwide. It can arise from a variety of diseases, with most resulting in a loss of cardiomyocytes that cannot be replaced due to their inability to replicate, as well as to a lack of resident cardiomyocyte progenitor cells in the adult heart. Identifying and exploiting mechanisms underlying loss of developmental cardiomyocyte replicative capacity has proved to be useful in developing therapeutics to effect adult cardiac regeneration. Of course, effective regeneration of myocardium after injury requires not just expansion of cardiomyocytes, but also neovascularization to allow appropriate perfusion and resolution of injury-induced inflammation and interstitial fibrosis, but also reversal of adverse left ventricular remodeling. In addition to overcoming these challenges, a regenerative therapy needs to be safe and easily translatable. Failure to address these critical issues will delay the translation of regenerative approaches. This review critically analyzes current regenerative approaches while also providing a framework for future experimental studies aimed at enhancing success in regenerating the injured heart.